SFL: Exploring Potential Meaning Directions from Thematic Structure Dominance in the National Song "Bagimu Negeri" - Yuwana, Rawuh Yuda; Riwu, Lay (Nusantara Journal of Multidisciplinary Science, 2024)
This research seeks to uncover the potential meanings stemming from the domination of thematic structure in the lyrics of the Indonesian national song "Bagimu Negeri." The study employs a descriptive qualitative method, focusing on sentences, clauses, stanzas, and individual words, using documentation techniques such as listening, recording, and note-taking. The collected data are analyzed through theme-rheme analysis, examining topical, textual, and interpersonal themes in detail. The analysis reveals a single dominant theme in the song's lyrics, with an unmarked topical theme predominating and no interpersonal themes present. The unmarked topical theme consistently serves as the subject. Furthermore, many stanzas in the lyrics lack a rheme. The thematic dominance suggests a strong expression of love for the homeland. This potential meaning likely reflects the intention of the lyricist, Kusbini, to demonstrate his profound love for the country and to inspire a similar sentiment in those who sing "Bagimu Negeri," particularly through the use of the word "we/kami." This expression is meant to instill and reinforce a sense of patriotism in every Indonesian citizen.